Environmental Biology - Fisher, Matthew R. (Open textbook library., 2018)
This open textbook covers the most salient environmental issues, from a biological perspective. The text is designed for an introductory-level college science course. Topics include the fundamentals of ecology, biodiversity, pollution, climate change, food production, and human population growth.